Weight loss diets advertised in non-scientific publications - Olga Maria Silverio Amancio; Daniela Maria Alves Chaud
Weight-loss diets advertised in mainstream non-scientific publications and targeting the adult female public were evaluated in relation to total energy value, macronutrients, calcium, iron, vitamins A and E, and cholesterol content, as well as the presence of information regarding the duration of diets, fluid intake, physical activity, and maintenance diets. Two publications were selected, considering periodicity, circulation, readership, and years in publication. The Virtual Nutri software was used to evaluate the nutrients of 112 diets. Micronutrient content was compared to the Dietary Reference Intakes. All diets were inadequate in at least one of the evaluated items. Less than 25.0% of the diets presented adequate macronutrient distribution. Calcium, iron, and vitamin E were also predominantly inadequate (85.7, 97.3, and 91.9%, respectively). Non-scientific publications should not be allowed to advertise weight-loss diets. In addition, their chemical composition is inadequate and they are not accompanied by important instructions for such therapy.